Strategi untuk Meningkatkan Daya Saing dan Minat Pembeli pada Toko Gadis Cakes Manna Bengkulu Selatan - Maghfira Fitria Sahara; Sazili Sazili (Universitas Dehasen Bengkulu, 2022)
The purpose of this study is to find out (1) the strategies used to increase competitiveness at the Gadis Cakes store (2) the strategies used to increase the interest of shoppers at the Gadis Cakes store. This research uses qualitative. The data sources in this study are Primary Data and Secondary Data. The data collection technique of this research used observation, interviews and documentation. The results of the study show that: (1) It can be said that the strategy used by the Girl Cakes Store is able to increase the competitiveness of micro-enterprises by providing products that are different from other stores such as cakes that cost thirty five thousand rupiah elsewhere, no one sells immediately. thirty five thousand rupiah but the girl cakes shop provides cakes at affordable prices, increasing the products that are in demand by consumers so that consumers are interested in buying these products. (2) What buyers are usually interested in is a cake product which costs thirty five thousand rupiah because this cake is quite affordable to consumers where the shoppers of this cakes girl shop are mostly teenagers who are still in school so that with the price of thirty five thousand rupiahs cakes make consumers more choose the product.